Ethnic Separatism - Williams, Colin (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1980)
The paper outlines the main characteristics of ethnic separatism as a process. It then analyses two theories designed to explain the resurgence of reactive peripheral identity, the Internal Colonial thesis and the role of the ethnic intelligentsia. Some of the inherent contradictions in the Parti Québécois's attempt to create a genuine Québécois nation through the promotion of French culture are explored as are some of the pitfalls of a referendum on Sovereignty-Association.